Vasculoprotective Effects of Pomegranate (Punica granatum L.) - Wang, Dongdong; Özen, Cigdem; Abu-Reidah, Ibrahim M.; Chigurupati, Sridevi; Patra, Jayanta Kumar; Horbanczuk, Jarosław O.; Jóźwik, Artur; Tzvetkov, Nikolay T.; Uhrin, Pavel; Atanasov, Atanas G. (Frontiers in Pharmacology, 2018)
Pomegranate (Punica granatum L.), one of the oldest known edible fruits, is nowadays broadly consumed throughout the world. Its fruits and seeds as well as other anatomical compartments (e.g., flowers and leaves) are rich in numerous bioactive compounds and therefore, the scientific interest in this plant has been constantly growing in recent years. It has been shown that pomegranate and its extracts exhibit potent antioxidative, antimicrobial and anticarcinogenic properties. The present review summarizes some recent studies on pomegranate, highlighting mainly its vasculoprotective role attributed to the presence of hydrolyzable tannins ellagitannins and ellagic acid, as well as other compounds (e.g., anthocyanins and flavonoids). These in vitro and in vivo studies showed that substances derived from pomegranate reduce oxidative stress and platelet aggregation, diminish lipid uptake by macrophages, positively influence endothelial cell function and are involved in blood pressure regulation. Clinical studies demonstrated that daily intake of pomegranate juice lessens hypertension and attenuates atherosclerosis in humans. Altogether, the reviewed studies point out the potential benefits of a broader use of pomegranate and its constituents as dietary supplements or as adjuvants in therapy of vascular diseases, such as hypertension, coronary artery disease and peripheral artery disease.